Answer:
Ba(OH)2 (aq) + H2SO4(aq) → BaSO4(s) + 2 H2O(l)
That's the right one.
Explanation:
You should see that this equation is balanced, not as
Ba(OH)2 (aq) + H2SO4(aq) → BaSO4(s) + H2O(l)
(on reactive we have 4 H, on products, we have only 2)
Ba(OH)2 (aq) + H2SO4(aq) → H2Ba(s) + SO4(OH)2(l)
(this is impossible, it's a nonsense)
BaSO4(s) + 2 H2O(l) → Ba(OH)2 (aq) + H2SO4(aq)
(it is the same with the right one but is the other way around. The statement says, reaction of Ba(OH)2 with H2SO4, not BaSO4 with water. Also, it is not a chemical balance.